Labial adhesion or fusion-an unusual cause of urinary incontinence in an elderly woman - Verma, Divya; Kumar, Sanjeev; Thakur, Abhishek; Adangale, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Labial adhesion/fusion is an uncommon cause of urinary and vulval complaints in adult females, with unknown incidence. We present a case report of an elderly woman who presented with voiding difficulty, recurrent urinary tract infection (UTI) and urinary incontinence. She was treated by surgical division of the adhesions and had complete resolution of her symptoms.